Credit for what? Informal credit as a coping strategy of market women in northern Ghana - Kati Schindler (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
This paper analyzes the use of informal credit as a coping strategy against risk by market women in the city of Tamale, Ghana. Using qualitative research techniques, the analysis reveals that intra-household structure and allocation decisions determine these market-based coping strategies. Market women invest a considerable amount of working hours in maintaining complex credit networks as a safeguard against extreme risks. As a policy implication, this research suggests to provide market women with access to formal, reliable and long-term microfinance institutions, both to improve their ability to cope with risks and to reduce the risks they face.
Keywords: O17; D13; O12; 330; micro-credit; informal markets; networks; coping strategies; intra-household allocation; women; Ghana